On the territorial conflicts of the 21st century. An interview to Hackitectura.net - Sánchez-Laulhé, José María (Universidad de Lima. Carrera de Arquitectura, 2020)
The collaborative group Hackitectura.net (2001-2010), due to its transgressive andexperimental nature, is only acknowledged by minority groups, despite having developed works and exhibitions in reference centers. One of the main points of this research consists in a series of interviews conducted with three of the Hackitectura.net core members (Sergio Moreno, José Pérez de Lama and Pablo deSoto). These interviews are aimed at contextualizing their work and the paradigm shift regarding the digitization and globalization taken place at the turn of the century. Their reflections enable us to project them on contemporary territorial conflicts.